The third sector and its impact on urban areas: the case of the new city Ali Mendjeli of Constantine - Fadel, Abdelouahab (Journal of Human Sciences, 2021)
The new city Ali Mendjeli is a functionally independent territory from the mother city Constantine. This is due to the importance and concentration of the tertiary sector, which has had a great influence on its urban dynamics. The economic sector of the new town includes simple commercial activities as well as high-end or superior shops. These latter - the focus of our study - are directly linked to the presence of equipment that has structured business activities in nature, type and hierarchy. The location of these commercial activities by specifying and showing the peculiarities of each, gave rise to neighborhood units of great importance or enhanced certain units over others. The new town can be considered a university town according to its university structures as well as a health town with a large number of facilities and activities in the health sector. These essentially university facilities